(untitled) (Revista de Estudos da Linguagem, 2024)
This paper aims to analyze the elaboration of grammars for the Portuguese and Spanish languages, describing textual and extratextual aspects that characterize this process in the respective linguistic traditions and comparing them in order to find points of convergence and divergence. For that purpose, by consulting the physical and electronic collections of different research centers, it was possible to build a bibliographic corpus which allowed the fulfillment of the study’s objective based on the analysis of 172 Portuguese and 138 Spanish grammars distributed since the 15th century. As a result, it was possible to observe that both codification traditions bring historical compatibilities which resulted in a process of linguistic normalization in which many features converge, while others diverge. They converge, for instance, in the intensification of this process from the 19th century onwards, marking a movement of constant growth. They diverge, on the other hand, in the number of countries engaged in the process and in the relation of school grammar to the descriptive model, for instance.